Craig Calhoun (ed.), Sociology in America: A History - Balon, Jan (Teorie vědy / Theory of Science, 2011)
Review: Craig CALHOUN (ed.). Sociology in America: A History. An ASA Centennial Publication. Chicago: University of Chicago Press 2007. 913 s.